LRH-1 agonism favours an immune-islet dialogue which protects against diabetes mellitus - Nadia Cobo-Vuilleumier (Nature Portfolio, 2018)
Type 1 diabetes mellitus (T1DM) is characterized by beta cell loss because of an autoimmune attack. Here the authors show that an agonist for LRH-1/NR5A2, a nuclear receptor known to be protective against beta cell apoptosis, inhibits immune-mediated inflammation and hyperglycemia in T1DM mouse models.